Encyclopedia of Life Sciences 2011
DOI: 10.1002/9780470015902.a0023179
|View full text |Cite
|
Sign up to set email alerts
|

Meganucleases and Their Biomedical Applications

Abstract: Homing endonucleases and zinc‐finger nucleases are double‐stranded meganucleases that target large deoxyribonucleic acid (DNA) recognition sites, a feature that means only a few such sites are likely to be present in a mammalian‐sized genome. Several homing endonucleases have been used as templates to engineer tools that cleave DNA sequences other than their original wild‐type targets. Indeed, zinc‐finger nucleases have been designed to recognise specific genes. These custom meganuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This indicates that it may be possible to generate several dozen unique DIMN-based transcription factors. In addition, several hundred meganucleases without known recognition sequences were also identified . Moreover, a recent study showed that it is possible to fuse or redesign meganucleases allowing the engineering of specific sequence recognition domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that it may be possible to generate several dozen unique DIMN-based transcription factors. In addition, several hundred meganucleases without known recognition sequences were also identified . Moreover, a recent study showed that it is possible to fuse or redesign meganucleases allowing the engineering of specific sequence recognition domains.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several hundred meganucleases without known recognition sequences were also identified. 34 Moreover, a recent study showed that it is possible to fuse or redesign meganucleases 35−37 allowing the engineering of specific sequence recognition domains. This concept was proven in a study aimed at producing a stable reduction in circulating PCSK9 and serum cholesterol levels by targeted gene disruption using an engineered meganuclease.…”
Section: ■ Discussionmentioning
confidence: 99%
“…HEs occur in nature across the mitochondrial and chloroplast genomes of eukaryotes (particularly plants, algae, fungi, and protozoans) and in the genomes of archaea, bacteria, and bacteriophages [ 6 , 7 ]. Meanwhile, synthetic meganucleases are produced by swapping or modifying domains from different HEs [ 8 , 9 ].…”
Section: Meganucleasesmentioning
confidence: 99%
“…They are double stranded DNases also called as homing nucleases that aim broad recognition sites, which stimulates effective gene targeting by double stranded break induced homologous recombination, leads to reform breaks in the DNA double strands. The engineered meganucleases adopted from microorganisms are altered to create double stranded breaks, which acts as a standard platform to direct the enzymes and exactly allow them to cleave the DNA at target site in the process of recombination (37). They are utilized to produce herbicide resistance and insect tolerance in cotton (38) and male sterility in maize (39).…”
Section: Engineered Meganucleases (Emns)mentioning
confidence: 99%